Eye injuries in badminton - players` perspective toward the usage of personal protective equipment - Maldoddi, R.; Gella, L. (The Physician and Sportsmedicine, 2024)
Objective We conducted a survey between April to September 2021 to understand the perspective of badminton players on the usage of personal protective equipment to avoid eye injuries.